An approximate and efficient characterization method for temperature-dependent parameters of thermoelectric modules. (15th January 2019) - He, Hailong; Liu, Weiwei; Wu, Yi; Rong, Mingzhe; Zhao, Peng; Tang, Xiaojun
Highlights: A simple test rig designed for multi-parameters adjustability and test reliability. A comprehensive model with all related effects considered is validated by tests. A quasi-steady state characterizing method for temperature-dependent properties. Correctness and feasibility of the method proved by simulation and test respectively. Abstract: Thermoelectric generator which converts waste heat to electricity is a promising approach in energy field. In this paper, a comprehensive numerical model of a thermoelectric couple is built by COMSOL with all related thermoelectric effects and some irreversible effects considered. It is adopted instead of a whole thermoelectric module modeling for a less calculation demanding and time consumption purpose, whose feasibility and equivalence are verified as well. An easy-manipulative symmetric test rig is designed to precisely acquire the electrical and thermal variables of thermoelectric module in terms of heat flow rate, voltage and current in a wide temperature range. The good agreement of test and simulation results validate the effectiveness of the numerical model and the feasibility of test device including its control and measurement systems. Then a novel characterization method called quasi-steady-state method is first proposed to fast and precisely derive the module-level temperature-dependent thermoelectric parameters including Seebeck coefficient S, thermal conductivity λ and electrical resistivity ρ . The characterization procedure is to raise the temperature of the thermoelectric module's hot side at an appropriate heating rate and keep the chiller at a constant temperature both in open and short circuit tests in sequence. The thermoelectric leg is regarded as multiple serial segments divided according to its temperature distribution. One set of equations involving the thermo- and electro- variables is established for each segment in case of a certain temperature difference. All these equations are solved by means of an iterative algorithm and computed by MATLAB. S and λ are obtained by open circuit tests and ρ by the short circuit tests subsequently. The comparison of estimated thermoelectric parameters by tests, simulations and the manufacturer's data validate the correctness of the quasi-steady-state method and its predictability ability of the performance of thermoelectric generators in practice.